The Effect of Using Powerpoint Media on The Ability to Solve Mathematical Problems of Flat Shapes - Nita Febriana Ma'rifatus Sa'adah; Vira Amalia Choirun Ni'mah; Hermawan Setia Budi; Lovika Ardana Riswari (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
This study aims to determine the effect of using Powerpoint media on the ability of fourth-grade students of SDN 2 Singocandi to solve mathematical problems based on Polya's theory. Based on the results of tests and interviews, it appears that student's ability to solve mathematical problems is still lacking. This research uses quantitative methods with a survey research type. The population in this study were fourth-grade students of SDN 2 Singocandi. The sample taken in this study was all students totaling 20 students. The sampling technique was carried out using a saturated sampling technique which was. Data collection techniques included written tests, interviews, and documentation. This research design is pre-test and post-test. The analysis technique used is the paired sample t-test analysis technique. The results showed that the use of PowerPoint learning media affected the skills of solving mathematical problems on flat material, which was categorized as (1) Students in the high category who can solve problems understand, plan, implement, and check answers by Polya's steps. (2) Students in the medium category can understand the problem, make a solution plan, and implement the plan, but do not check the answer. (3) Students in the low category were unable to solve the problem according to the steps of Polya's theory.